Correction of Aberrant NADPH Oxidase Activity in Blood-Derived Mononuclear Cells from Type II Diabetes Mellitus Patients by a Naturally Fermented Papaya Preparation - Dickerson, Ryan (Mary Ann Liebert, Inc., 2012)
Supplementation of standardized fermented papaya preparation (FPP) to adult diabetic mice improves dermal wound healing outcomes. Peripheral blood mononuclear cells (PBMC) from type II diabetes mellitus (T2DM) patients elicit a compromised respiratory burst activity resulting in increased risk of infections for the diabetic patients. Aims: The objectives of the current study were to determine the effect of FPP supplementation on human diabetic PBMC respiratory burst activity and to understand underlying mechanisms of such action of FPP. Results: When stimulated with phorbol 12-myristate 13-acetate, the production of reactive oxygen species by T2DM PBMC was markedly compromised compared to that of the PBMC from non-DM donors. FPP treated ex vivo improved respiratory burst outcomes in T2DM PBMC. FPP treatment significantly increased phosphorylation of the p47phox subunit of NADPH oxidase. In addition, the protein and mRNA expression of Rac2 was potently upregulated after FPP supplemention. The proximal human Rac2 gene promoter is G–C rich and contains consensus binding sites for Sp1 and AP-1. While FPP had no significant effect on the AP-1 DNA binding activity, the Sp1 DNA binding activity was significantly upregulated in PBMC after treatment of the cells with FPP. Innovation: This work provided first evidence that compromised respiratory burst performance of T2DM PBMC may be corrected by a nutritional supplement. Conclusion: FPP can correct respiratory burst performance of T2DM PBMC via an Sp-1-dependant pathway. Studies testing the outcome of FPP supplementation in diabetic patients are warranted. Antioxid. Redox Signal. 17, 485–491.